Métodos numéricos do tipo Runge-Kutta para solução de equações diferenciais ordinárias (EDOS) - LIMA NETO, José Sousa (2022)
Some numerical methods, known in the literature, for solving the simple pendulum problem are presented. The methods were compared using the results obtained in the numerical solution. A new method was proposed, presenting better results than traditional methods.